Study of Excavation Volume Calculation Using Mapping Application in Irrigation Network Modernization Activities - Pratama, Imron Sigit; Saily, Randhi; Jusi, Ulfa; Lyona, Vinka; Kurniyaningrum, Endah (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
The modernization of irrigation networks is a vital effort to improve the efficiency and effectiveness of water distribution for agriculture. This activity also represents the implementation of the government’s Asta Cita program in the context of national food security. One critical component of this process is excavation work, which significantly influences the success of such projects. This study aims to evaluate the accuracy of several interpolation methods in calculating excavation volumes based on design data, compared to existing conditions, using a tolerance threshold of 2.78%. The analysis indicates that interpolation methods produce varying results. The Kriging method shows a deviation of 2.30%, and the Surface to Surface (TIN) method shows a deviation of only 0.02%, both of which fall within acceptable deviation limits. These two methods also demonstrate high consistency and optimal accuracy for volume estimation. In contrast, methods such as Natural Neighbor (18.89%) and Radial Basis Function (RBF) (46.17%) result in significant deviations, indicating overestimation or underestimation that affects volume accuracy. Therefore, methods like Kriging and TIN, which meet the tolerance limits, are recommended for more accurate and efficient volume calculations in construction and topographic mapping activities.